Analyzing the Relationship Between Cultural Diversity, Social Capital, and Community Resilience in Jakarta, Indonesia - Endang Supriatna; Dhiana Ekowati; Adit Mohammad Aziz; Sabil Mokodenseho (Eastasouth Institute, 2023)
In Jakarta, Indonesia, this study explores the complex interrelationships among social capital, cultural diversity, and community resilience. Participants from a varied sample of 500 people, spanning a range of socioeconomic classes, and nationalities, shared their perspectives on social capital, cultural diversity, and community resilience. The results show a culturally diversified and affluent community where people feel they have strong social ties and are resilient. Indicators of community resilience, social capital, and cultural variety all show favorable connections according to statistical analysis. Regression analyses highlight the important roles that cultural variety, social capital that bonds, bridges, and links, and environmental, social, and economic resilience play in enhancing the overall resilience of Jakarta's communities. The sample's diversity in terms of demographics improves the findings' external validity. This research offers significant perspectives for practitioners and policymakers that aim to promote resilience in urban environments with various cultural backgrounds.